2019
DOI: 10.15361/1984-5529.2019v47n3p321-326
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of forage pea seed lots by means of multivariate techniques

Abstract: Multivariate techniques allow to understand the structural dependence contained in the variables, as well as to characterize groups of seed lots according to specific standards. Thus, this study analyzes the efficiency of multivariate exploratory techniques in discriminating forage pea seed lots as a function of the physiological potential of seeds. We evaluated ten seed lots of forage pea in a completely randomized design, considering the following variables: thousand seed weight, germination, first germinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…In red rice seeds, the electrical conductivity test showed a strong relationship with the emergence of seedlings in the field (Table 4) and provided early important information about its physiological potential. Some authors found that the electrical conductivity test also showed highly significant correlation with seedling emergence in the field for several species, such as peanut (BARBOSA et al, 2012), graniferous sorghum (MARCOS; DUTRA, 2018), and forage pea (MACHADO et al, 2019). Thus, coherence between the electrical conductivity results and performance in the field was established, as this is a premise for the effectiveness of a vigor test, because of limitations of the germination test.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In red rice seeds, the electrical conductivity test showed a strong relationship with the emergence of seedlings in the field (Table 4) and provided early important information about its physiological potential. Some authors found that the electrical conductivity test also showed highly significant correlation with seedling emergence in the field for several species, such as peanut (BARBOSA et al, 2012), graniferous sorghum (MARCOS; DUTRA, 2018), and forage pea (MACHADO et al, 2019). Thus, coherence between the electrical conductivity results and performance in the field was established, as this is a premise for the effectiveness of a vigor test, because of limitations of the germination test.…”
Section: Resultsmentioning
confidence: 99%
“…The electrical conductivity test meets these characteristics and has great potential, because it is a fast method and benefits both industries and farmers alike (PRADO et al, 2019). It has been useful in the evaluating the seed vigor of several species such as common bean (LEÃO et al, 2012), peanut (BARBOSA et al, 2012, graniferous sorghum (MARCOS; DUTRA, 2018), forage pea (MACHADO et al, 2019), andsoybean (PRADO et al, 2019). However, there is no specific information in previous literature on the methodology of the electrical conductivity test for red rice seeds.…”
Section: Introductionmentioning
confidence: 99%
“…The principal component analysis of the soybean seed treatments was adequate, as the values of the principal components were similar to those found in studies evaluating soybean seed lots [ 28 ] and safflower vigor tests [ 29 , 30 ]. According to [ 31 ], a relatively small number of components were extracted (PC1 and PC2), with the ability to explain the highest variability in the original data.…”
Section: Discussionmentioning
confidence: 99%
“…The multivariate data analysis methods allow a global study of these variables, evidencing the connections, similarities, or differences between them with the least possible loss of information [ 26 , 29 , 30 , 31 , 34 ].…”
Section: Discussionmentioning
confidence: 99%